Effects of Proteasome Inhibitor on Catalase Expression and Intima-media Thickness in the Aorta of Atherosclerotic Rats - Ismawati Ismawati; Enikarmila Asni; Ilhami Romus; Mukhyarjon Mukhyarjon; Winarto Winarto; Muhammad Fadhillah Arif; M Derillovyandra Dwi Anugrah (Global Medical & Health Communication (GMHC), 2022)
Various studies have been carried out to obtain proper management for atherosclerosis. Proteasome, a subcellular enzyme complex, is a potential therapeutic target for atherosclerosis. However, the effect of proteasome inhibitors on atherosclerosis still needs to be explored. It was an experimental study with a post-test-only control group design conducted at the Faculty of Medicine, Universitas Riau in Juni–November 2021. This study aimed to analyze the effects of proteasome inhibitors on catalase expression and intima-media thickness (IMT) in the thoracic aorta of atherosclerotic rats. Fifteen male Wistar rats were randomly divided into three groups (five rats per group), namely rats given standard feed (control, group I), rats induced atherosclerosis (group II), and rats induced atherosclerosis and given proteasome inhibitor (group III). The proteasome inhibitor, bortezomib, 50 µg/kgBW/day was given intraperitoneally on days one and three. After 4 days, rats were terminated, and the thoracic aorta was taken for the IMT analysis and catalase expression assessment using immunohistochemistry. Catalase expression was carried out quantitatively using Adobe Photoshop software. Analysis of variance test was used to compare the expression of catalase and IMT. A p value<0.05 was considered statistically significant. The results showed a significant decrease in IMT in group III compared to group II and an increase in catalase expression in group III compared to group II but not statistically significant. This study concludes that administration of bortezomib 50 µg/kgBW in atherosclerotic rats could inhibit thickening tunica intima-media in the thoracic aorta, although not significantly increasing the catalase expression.